RESPONS PERTUMBUHAN DAN PRODUKSI BEBERAPA VARIETAS TANAMAN JAGUNG TERHADAP PEMBERIAN PUPUK N DAN K - Pandia, Abdurrahman; Bangun, Mbue Kata; Hasyim, Hasmawi (Universitas Sumatera Utara, 2013)
The use of Central Composite Rotatable Design (CCRD) to determine the response surface yield at maize not yet a lot of checked, for that an research have been conducted in UPT BBI Tanjung Selamat, Regency of Deli Serdang, Province of North Sumatra with the land height ± 25 m above sea level, at May 2012 - August 2012.The design was used is randomized block design with two factors, the first factor is two varieties (Bisma and SHS-4) and the second factor is fertilizer NK (the dose of NK determined from CCRD). Parameters measured were: plant height, the number of leaf, the number of leaf above cob, the time of tasselling, the time of silking, the time of harvesting, the rate seed filling, cob lenght, cob diameter, the number of lines per cob, the number of seeds per cob, weight of 100 seeds and production of dry seeds. The results showed that the varieties significantly on plant height, the number of leafs, the time of harvesting and dry seeds production. Fertilizer sigificantly on production of dry seeds. Interaction of varieties and fertilizer NK significantly on production of dry seeds. Keywords : maize, NK fertilizer, varieties, CCRD.